Interplay of anion-pi(+) and pi(+)-pi(+) interactions in novel pyrido[2,1-a]isoquinolinium-based aiegens - substituent- and counterion-dependent fluorescence modulation and applications in live cell mitochondrial imaging - Mule, Ravindra D.; Roy, Rupam; Mandal, Koushik; Chopra, Deepak; Dutta, Tanoy; Sancheti, Shashank P.; Shinde, Popat S.; Banerjee, Somsuvra; Lal Koner, Apurba; Bhowal, Rohit; Senthilkumar, Beeran; Patil, Nitin T. (Chemistry-A European Journal, 2022)
Recently, the concept of anion-pi(+) interactions has witnessed unique applications in the field of AIEgen development. In this contribution, we disclose a consolidated study of a library of N-doped ionic AIEgens accessed through silver-mediated cyclization of pyridino-alkynes. A thorough photophysical, computational and crystallographic study has been conducted to rationalize the observed substituent- and counterion-dependent fluorescence properties of these luminogens. We further elucidate the prominent role of anion-pi(+) interactions, pi(+)-pi(+) interactions and other non-covalent interactions, in inhibiting the undesired ACQ effect. Finally, we have also demonstrated the application of selected AIEgens for imaging of mitochondria in live cells.
Keywords: 1-a]isoquinolinium; AIEgens; anion-pi(+); crystal structure; mitochondrial imaging; pyrido[2